(untitled) (The International Journal for Scientific Research, 2023)
This study aimed to investigate the effects of Cactus (Aloe vera) leaf powder and gel on the productive performance and some characteristics of broiler carcasses. A total of 288 one-day-old broiler chicks (Ross -308) were randomly distributed among eight treatments, three replicates, and 12 birds per each replicate according to the complete random design (CRD). The first treatments were fed a basal diet (BD) and considered as a control treatment. The second treatment was fed BD supplemented with Neomycin as an antibiotic at 0.5 g/kg. Third, fourth, and fifth treatments were fed BD supplemented with Aloe vera powder at 5, 15, and 30 g/kg. Aloe vera gel at levels 5, 15, and 30 (ml/l) was administrated in drinking water to treatments sixth, seventh, and eighth respectively. Results indicated a significant improvement (P≤0.05) in final body weight (except T2 and T6) and total weight gain (except T6) for all supplemented treatments comparison to control. There was a significant decrease (p≤0.05) in total feed intake for all supplemented treatments as compared to the control, while there was a significant improvement in total feed conversion ratio in all supplemented treatments compared to the control. A significant increase (p≤0.05) in total water consumption in the T3, T4, T5 and T8 treatments as compared to control, and T2, T6, and T7, as well, a significant increase in the ratio of water consumption to feed for all supplemented treatments as compared with control. A significant increase (p≤0.05) in carcass weight and dressing percentage for all supplemented treatments except T2 and T6 as compared with the control. The performance index, production index, and protein efficiency ratio significantly were better than the control. In conclusion, Aloe vera leaf powder (5, 15, 30 g/kg) to broiler diets and leaf jell in drinking water (15 and 30 ml/l), could be used to improve production performance, carcass traits, performance index, production index, and protein efficiency ratio. The study also confirms that supplemented with 5 (g /kg) of Aloe vera leaf powder and 15-30 (ml /liter) of gel could be a successful alternative to the antibiotic Neomycin (0.5 g/ kg) in broiler diets.